Building information : modeling (BIM) roles in the Malaysian construction industry - Ahmad Latiffi, Aryani (2014)
Building Information Modeling (BIM) represents a new paradigm in the Malaysian architecture, engineering, and construction (AEC) industry. BIM technology provides virtual models (including 3-D models) to generate a building’s entire lifecycle. The model can also be used for analyzing design clashes, project scheduling, cost estimation, and facility management. The use of BIM in construction projects can reduce time to develop a project, reduce construction cost, and increase project quality. This paper aims to explore roles of BIM in the Malaysian construction industry. Semi-structured interviews were conducted with project consultants and BIM consultants involved in two government projects. The projects were the National Cancer Institute (NCI) Malaysia and Sultan Ibrahim Hall (formerly known as the Multipurpose Hall of Universiti Tun Hussein Onn Malaysia, or UTHM). The interviews revealed effects of BIM in both projects and potential improvement in implementing BIM in construction projects in Malaysia. A literature review and the interviews revealed that BIM is increasingly used and accepted by construction players in Malaysia, and is expected to grow in future